Computer modeling of the process of overturning of the automobile - Sokolovskij, Edgar (Transport, 2007)
The article deals with investigation of the possibilities of the program PC CRASH, meant for the computer modeling of the movement of vehicles. The computer modeling of the process of overturning of the automobile with the help of the program PC CRASH is introduced. The cross profile of the road, the height of the centre of gravity of the automobile and the other parameters are evaluated while modeling. The influence of the introduced parameters upon the computer modeling results is investigated. The possibilities of application of the computer modeling programs in the expert assessment of the traffic accidents are considered, the items on reliability of the results of modeling and the requirements, raised towards the experts, who work with such programs, are analyzed.First Published Online: 27 Oct 2010